Tube Wave removal from vertical seismic profiling (VSP) surveys - Nadri, D.; Urosevic, Milovan; Wilkes, P.; Asgharzadeh, Mehdi (CSIRO, 2012)
This paper presents a processing workflow to attenuate the strong tube waves from VSP surveys acquired in Perth, Western Australia. An array of 24 hydrophones spaced at 10 metre intervals is attached to a cable run down the borehole. The hydrophones were unclamped, so they record significant amount of the tube waves which entirely mask the upgoing waves. F-K filtering was used for wavefield decomposition of flattened downgoing waves. Linear moveout correction was applied to flatten the tube waves and removed unusual aliased energy due to shot depth variations and hydrophone positioning errors through the F-K filtering. The flattened data were transformed to tau-pi domain using a very narrow window slowness to produce a model of tube waves. An adaptive wavefield subtraction algorithm was used to subtract the tube wave model using a matching filter from the input data. The result was processed through a F-K filter and moderate tau-pi filter to remove the residual undesired energy. After attenuating the multiple energy and true amplitude recovery, pre stack depth migration, a CDP-VSP mapping and stacking were applied to produce CDP equivalent depth and time images.